Władysław Kuraszkiewicz – uczony i nauczyciel - Walczak, Bogdan (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The author presents the life and work of professor Władysław Kuraszkiewicz, especially pointing to his works concerning east Slavic languages and dialects, with a particular emphasis in Ukrainian. He also highlights studies of the history of Polish literary language, didactic and pedagogic presentation of professor Kuraszkiewicz as a creator of the Poznań school of historical linguistics.